2016
DOI: 10.1021/acs.orglett.6b03378
|View full text |Cite
|
Sign up to set email alerts
|

Double Chiral Induction Enables a Stereoselective Carbonyl Allylation with Simple Alkenes under the Sequential Catalysis of Palladium Complex and Chiral Phosphoric Acid

Abstract: An enantioselective carbonyl allylation of aldehydes with simple alkenes has been achieved via a one-pot protocol consisting of a Pd-catalyzed allylic C-H borylation with bis(pinanediolato)diboron and a chiral Brønsted acid catalyzed asymmetric allylborylation, delivering homoallylic alcohols in high yields and with excellent diastereo- and enantioselectivities. The double chiral induction of chiral allylic borate and chiral phosphoric acid allows the reaction to give excellent stereoselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…The Gong group has also been active in the same area as Murakami and Miura: transition-metal-catalyzed allylboronate formation followed by the sequential allylboration of aldehydes. 64,65 In 2015 the group published their first example, in which they use a palladium catalyst to activate an allylic C-H bond to form an allylboronate 2, which in the presence of an aldehyde reacts to form the corresponding anti-homoallylic alcohol 5. 64 The proposed reaction mechanism involves a phosphoric acid binding to the palladium center, and this is thought to be the species responsible for C-H activation; the phosphate can abstract the allylic hydrogen to regenerate the phosphoric acid, leaving the allyl anion coordinated to the palladium (Scheme 36).…”
Section: Review Syn Thesismentioning
confidence: 99%
See 1 more Smart Citation
“…The Gong group has also been active in the same area as Murakami and Miura: transition-metal-catalyzed allylboronate formation followed by the sequential allylboration of aldehydes. 64,65 In 2015 the group published their first example, in which they use a palladium catalyst to activate an allylic C-H bond to form an allylboronate 2, which in the presence of an aldehyde reacts to form the corresponding anti-homoallylic alcohol 5. 64 The proposed reaction mechanism involves a phosphoric acid binding to the palladium center, and this is thought to be the species responsible for C-H activation; the phosphate can abstract the allylic hydrogen to regenerate the phosphoric acid, leaving the allyl anion coordinated to the palladium (Scheme 36).…”
Section: Review Syn Thesismentioning
confidence: 99%
“…In 2017 the Gong group published another report focusing on the same reaction sequence, but using a double chiral induction strategy; the use of chiral boronates 87 as well as a chiral catalyst 7 (Scheme 37). 65 This time the enantioselectivities were much higher, with many examples of products with over 90% ee. Interestingly, unlike previous reports in which 2,4,6-triisopropylphenyl-substituted TRIP 7a has always provided the best enantioselectivity, the group reports the best results with the 9-anthryl-substitut-…”
Section: Review Syn Thesismentioning
confidence: 99%
“…Over the past decades, continuous endeavors have been devoted to this field and revealed that sulfoxides, nitrogen ligands, N-heterocyclic carbenes, binaphthols, and some trivalent phosphorus ligands are capable of accelerating Pd-catalyzed allylic C–H functionalization, culminating in the rise of a diverse range of transformations, including oxidations, , aminations, alkylations, fluorination, dehydrogenation, olefination, and even the related enantioselective version . A ground-breaking example of asymmetric allylic C–H activation was reported by Covell and White in 2008, who described the enantioselective allylic C–H acetoxylation of α-alkenes by using a chiral chromium Lewis acid bound with BQ to induce stereoselectivity during nucleophilic attack (Scheme ); however, branched allylic acetate products were obtained with only moderate levels of enantioselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst them, oxidative borylation seemed to be the most promising strategy with moderate condition and low cost (Scheme 11 ). Hydroxyalkyl derivatives of different configurations can be obtained by employing different diborides and chiral phosphoric acids as ligands [ 102 , 103 ]. Allyl-benzene fragments can also be diastereoselectively hydroxyalkylated catalyzed by ruthenium and iridium catalysts through a cross-metathesis/ isomerization/allylboration sequence [ 104 ].…”
Section: Structural Derivatization Strategies Of Natural Phenols By S...mentioning
confidence: 99%